2018
DOI: 10.1007/s00240-018-1076-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of ‘dusting and pop-dusting’ using a high-powered (100 W) laser machine in the treatment of large stones (≥ 15 mm): prospective outcomes over 16 months

Abstract: Ureteroscopy and laser stone fragmentation (URSL) has had recent advancements with the more powerful laser systems with the ability to 'dust' and 'pop-dust' the stone. We wanted to look at the outcomes of this method for large stones (≥ 15 mm) using our new 100 W holmium laser. Over a period of 16 months (January 2017-April 2018), 50 patients underwent URSL for minimum cumulative stone size of ≥ 15 mm. Data were collected prospectively on patient and stone demographics and outcomes of URSL. The laser setting u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Second, apply "high-frequency" setting with more caution. Previous study have showed that dusting maneuver with higher frequency can acquire better stone free rates for renal calculi [15]. Even though the dusting maneuver is more timeconsuming and will produce more heat, the renal pelvis can disperse the heat quickly because of its larger space comparing with ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Second, apply "high-frequency" setting with more caution. Previous study have showed that dusting maneuver with higher frequency can acquire better stone free rates for renal calculi [15]. Even though the dusting maneuver is more timeconsuming and will produce more heat, the renal pelvis can disperse the heat quickly because of its larger space comparing with ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, from the analysis of clinical cases, the mean length of pedal activation was found to be relatively short-3.6 seconds. Although high-power laser techniques have clinical advantages, 12,13 urologist need to be mindful of ODC and keep pedal activation times as short as possible.…”
Section: Effects Of Laser Activation Patterns On Fluid Temperaturementioning
confidence: 99%
“…The introduction of modern high-power lasers with newer lasertripsy methods has allowed treating large renal stones in complex patients with a reduced operating time [8]. The safety in high-risk patient groups is now well established and the use use of peri-operative antibiotics, access sheath usage, method of stone treatment and the use of postoperative stent.…”
Section: Discussionmentioning
confidence: 99%